2019
DOI: 10.1097/pgp.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

HPV 6-associated HSIL/Squamous Carcinoma in the Anogenital Tract

Abstract: Human papillomavirus (HPV) type 6 is historically classified as low-risk HPV type and associates with low-grade squamous intraepithelial lesions of the anogenital tract. Rare squamous carcinomas have been reported in association with these HPV types but the mechanism(s) behind this carcinogenic sequence have been unclear. We report 4 cases of low risk anogenital HPV infections—3 cervical (immature low-grade squamous intraepithelial lesion with metaplastic phenotype) and one anal (exophytic condyloma) lesion—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…and Guimera et al also showed impressive findings that p16-negative HPV6-associated cervical SCCs were verruco-papillary lesions on gross and papillary 19 SIL or well-differentiated morphology according to a histological examination. 15, Our case was similar to these previously reported cases. These findings suggest that cervical SCCs with low-risk HPVs show a well-differentiated morphology and are difficult to diagnose.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…and Guimera et al also showed impressive findings that p16-negative HPV6-associated cervical SCCs were verruco-papillary lesions on gross and papillary 19 SIL or well-differentiated morphology according to a histological examination. 15, Our case was similar to these previously reported cases. These findings suggest that cervical SCCs with low-risk HPVs show a well-differentiated morphology and are difficult to diagnose.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism behind carcinogenesis with low-risk HPVs is unclear, but some cervical SCCs are reported to have an association with low-risk HPVs. 15,21 Liu et al reported three cases of p16 negative HPV6-associated HSIL/SCCs in the uterine cervix. 15 Guimera et al reported 6 9 cases of cervical SCCs with low-risk HPVs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations